2018
DOI: 10.1002/pmic.201800101
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Profiles of Head Kidney and Spleen of Rainbow Trout (Oncorhynchus Mykiss)

Abstract: The head kidney and spleen are major lymphoid organs of the teleost fish. The authors identify proteome profiles of head kidney and spleen of rainbow trout (Oncorhynchus mykiss) using a shotgun proteomic approach. Gene ontology annotation of proteins is predicted using bioinformatic tools. This study represents detailed proteome profiles of head kidney and spleen of rainbow trout, with a total of 3241 and 2542 proteins identified, respectively. It is found that lymphoid organs are equipped with a variety of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In fish, the spleen and kidney have important functions in implementing immune defence and the maintenance of a stable internal environment (Kumar et al, 2018). In the kidney, both chronic and acute intoxication of cadmium have been indicated to cause nephropathies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fish, the spleen and kidney have important functions in implementing immune defence and the maintenance of a stable internal environment (Kumar et al, 2018). In the kidney, both chronic and acute intoxication of cadmium have been indicated to cause nephropathies.…”
Section: Discussionmentioning
confidence: 99%
“…Although cadmium levels were still higher than in the control group, this finding can be accepted as a protective effect of melatonin against cadmium accumulation in tissues. According to Chwełatiuk et al (2006), Hussein et al 2014 The accumulation of cadmium in the kidney and spleen as the organs of the haematopoietic system may disturb hematopoietic processes (Taheri et al, 2016;Kumar et al, 2018). Kondera and Witeska (2013) and Sun et al (2019) reported that cadmium reduced the hematopoietic potential in common carp (Cyprinus carpio L.) and yellow catfish (Pelteobagrus fulvidraco) in the head kidney and spleen, and caused histological lesions, antioxidative and inflammatory responses in both tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In zebrafish, 3,024 proteins were reported [77], 939 in three-spined sticklebacks (Gasterosteus aculeatus) [78], and 717 in Atlantic cod (Gadus morhua) (identification based on a minimum of one peptide for all three species) [79]. Interestingly, regarding other tissues and biofluids of rainbow trout, 3,241 proteins were reported in head kidney (identification based on a minimum of two peptides), 2,542 in spleen (identification based on a minimum of two peptides) [80], 59 in ovarian fluid (identification based on a minimum of two unique peptides) [81] and 152 in seminal plasma [82]. Differences in the number of protein identifications can have both biological (fish tissues and fluids used) and technical origin (sample processing, fractionation strategy, MS instrument type, data acquisition parameters, data trimming and database identification version and parameters).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, an intense expression of lep and lepr was observed in spleen and head kidney of C. punctata though the pattern varied from secondary to primary lymphoid organ. Recent studies in fishes have also shown marked difference between spleen and head kidney with respect to expression pattern of immune-related genes and their respective proteins in response to bacterial infection [34][35][36] . These differences have been attributed to differential role of primary and secondary lymphoid organs as teleostean spleen is proposed to be majorly involved in cellular responses while head kidney in humoral responses 34 .…”
Section: Discussionmentioning
confidence: 99%